ANALISIS PERAN GAYA KEPEMIMPINAN, PELATIHAN DAN KOMUNIKASI TERHADAP MOTIVASI KERJA KARYAWAN - Siska Yuli Anita (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research aims to find out the role of leadership style applied by the chairman of KUD, training that has been followed by employees, and communication between the chairman and employees to work motivations in KUD Citra Sawit Mandiri, Sumber Deras Village, Mesuji Subdistrict. Conducted on the chairman and employees of KUD Citra Sawit Mandiri, using qualitative research methods. Data collection techniques with interviews, observations, and documentation. The results showed that the leadership style used by the chairman of KUD Citra Sawit Mandiri to motivate employee work is a democratic leadership style, which is by the cooperative principle, namely the family principle. For training, KUD Citra Sawit Mandiri employees have participated in some training that is often done in the company and related to communication between KUD chairmen often provide regular feedback to employees by scheduling discussions in person.